2009
DOI: 10.1016/j.placenta.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Centrality of the Umbilical Cord Insertion in a Human Placenta Influences the Placental Efficiency☆

Abstract: Goal: We assess the effect on placental efficiency of the non-centrality of the umbilical cord insertion and on chorionic vascular distribution to determine if cord centrality measurably affects placental function as reflected in birth weight. Materials and Methods:1,225 placentas collected from a prospective cohort had digital photographs of the chorionic plate. Of these, 1023 were term, 44 had velamentous cord insertion and 12 had missing clinical data, leaving N=967 (94.5 %) cases for analysis. Mathematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 20 publications
8
79
3
1
Order By: Relevance
“…The largest distance from the point of centrality is a high risk factor to term LBW in our population. Our results suggest that such a shift may indeed affect nutrient supply to the fetus, probably from changes in the vascular tree surface area required for nutrient transport to the fetus [23]. However, further research is necessary to establish if this observation is seen in other study populations.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The largest distance from the point of centrality is a high risk factor to term LBW in our population. Our results suggest that such a shift may indeed affect nutrient supply to the fetus, probably from changes in the vascular tree surface area required for nutrient transport to the fetus [23]. However, further research is necessary to establish if this observation is seen in other study populations.…”
Section: Discussionmentioning
confidence: 69%
“…Previous reports have suggested that a shift in the centrality of the umbilical cord insertion on the chorionic plate reflects the level of vasculature available for nutrient supply [17,23]. Thus, a greater shift leads to a lower level of vascular distribution available for nutrient exchange (and vice versa) [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no difference in the overall mode of delivery for the cord, entangled, or non-entangled and all twins, although cord entanglement was more prevalent in spontaneous vertex vaginal deliveries [8].…”
Section: Umbilical Cord Lengthmentioning
confidence: 81%